Method for manufacturing secondary battery laminate
By forming an appropriate amount of adhesive material on the bonding surface of the electrode and the spacer during the manufacturing process of the secondary battery, and avoiding the bonding surface of the adhesive material from contacting other components, the problem of adhesion of the battery member is solved, and efficient laminate manufacturing is achieved.
Patent Information
- Application Number
- CN202411889003.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-02-26
- Filing Date
- 2019-02-01
- Publication Date
- 2025-04-01
AI Technical Summary
During the manufacturing process of the secondary battery, the battery member with the adhesive layer is prone to stick to it when wound and stored, resulting in the need to peel off the adhesive layer when manufacturing the laminated body, reducing productivity.
By forming an appropriate amount of adhesive material on the bonding surface of the electrode and the spacer, and avoiding contact between the bonding surface of the adhesive material with other components before bonding, ensuring sufficient bonding between the electrode and the spacer.
The efficient bonding between the electrode and the spacer is achieved, the manufacturing efficiency of the laminated body for secondary batteries is improved, and the adhesion problem is avoided.
Smart Images

Figure CN119742411A_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent application with application number 201980011351.3. The application date of the original application is February 1, 2019, and the name of the invention is “Method for manufacturing a laminate for secondary batteries”. Technical Field
[0002] The present invention relates to a method for producing a laminate for a secondary battery. Background Art
[0003] Secondary batteries such as lithium-ion secondary batteries are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. In addition, secondary batteries generally have battery components such as a positive electrode, a negative electrode, and a separator that separates the positive electrode from the negative electrode to prevent a short circuit between the positive electrode and the negative electrode.
[0004] Here, in the manufacturing process of the secondary battery, the electrode and the separator before being immersed in the electrolyte are sometimes pressed together to form a laminate (hereinafter sometimes referred to as a "laminate for secondary batteries"), which is cut into a desired size as needed, and stacked, folded or wound. Moreover, when cutting, stacking, folding or winding, the pressed electrode and the separator are sometimes misaligned, resulting in problems such as defects and reduced productivity.
[0005] Therefore, in recent years, a technology has been proposed for making the electrode and the separator well bonded in the manufacturing process of the secondary battery by using a separator having an adhesive layer on the surface. Specifically, for example, in Patent Document 1, a coating solution containing inorganic particles and a binder polymer is applied to a porous substrate and dried to form a porous coating layer, and then a binder solution having a specified surface energy and contact angle is applied to the surface of the porous coating layer and dried, thereby manufacturing a separator having a porous coating layer and an adhesive layer on a porous substrate for assembling a secondary battery.
[0006] Furthermore, generally, a battery member having an adhesive layer, such as a separator having an adhesive layer, is stored in a rolled state after forming the adhesive layer and before being used to form a laminate for a secondary battery (see, for example, Patent Document 2).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application No. 2014-534570;
[0010] Patent document 2: Japanese Patent Application Publication No. 2015-41603. Summary of the invention
[0011] Problem that the invention aims to solve
[0012] However, when the battery components with the adhesive layer are stored in a state of being wound into a roll, the battery components adjacent to each other through the adhesive layer will adhere (stick). Moreover, when the battery components are adhered to each other, when the battery components with the adhesive layer are fed out from the roll to manufacture the secondary battery stack, it is necessary to peel off the adhered battery components from each other, which will peel off the adhesive layer, thereby reducing productivity.
[0013] Therefore, an object of the present invention is to provide a method for efficiently producing a laminate for a secondary battery in which electrodes and separators are bonded together, while ensuring the adhesive force between the electrodes and the separators.
[0014] Solutions for solving problems
[0015] The inventors have conducted in-depth research for the purpose of solving the above technical problems. Then, the inventors found that when manufacturing a secondary battery stack formed by laminating an electrode and a spacer, if the amount of the adhesive material formed on the laminating surface is within a specified range, and after the adhesive material is formed, the electrode and the spacer are laminated without making the laminating surface formed with the adhesive material contact with other components, the adhesion between the electrode and the spacer can be ensured and the secondary battery stack can be manufactured efficiently, thereby completing the present invention.
[0016] That is, the object of the present invention is to advantageously solve the above-mentioned problem. The manufacturing method of the secondary battery stack of the present invention is characterized in that the manufacturing method of the secondary battery stack formed by bonding the electrode and the separator comprises: step (A), forming an adhesive material on the bonding surface of the above-mentioned electrode and at least one of the above-mentioned separators; step (B), after the above-mentioned step (A), the above-mentioned electrode and the above-mentioned separator are transported to the bonding start position without making the bonding surface formed with the above-mentioned adhesive material contact with other components; step (C), after the above-mentioned step (B), the above-mentioned electrode and the above-mentioned separator are bonded via the above-mentioned bonding surface, and the formation amount of the above-mentioned adhesive material in the above-mentioned step (A) is 0.1g / m 2 Above and 100g / m 2 As described above, if the amount of the adhesive material formed in step (A) is within a predetermined range, and the electrode and the separator are bonded together without making the bonding surface on which the adhesive material is formed contact with other components in steps (B) and (C), the electrode and the separator can be sufficiently bonded together, and compared with a case where the battery component (electrode and / or separator) on which the adhesive material is formed is temporarily wound into a roll for storage, etc., a laminate for a secondary battery can be efficiently manufactured.
[0017] Here, in the present invention, "bonding start position" refers to the position where the bonding surface of the electrode contacts the bonding surface of the spacer when the electrode and the spacer are bonded. In addition, in the present invention, "the amount of adhesive material formed" refers to the amount of adhesive material formed on the bonding surface per unit area, which can be calculated by dividing the mass of the adhesive material formed on the bonding surface by the area of the bonding surface on which the adhesive material is formed. In addition, "the area of the bonding surface" refers to the area of the portion that contacts each other when the electrode and the spacer are bonded (that is, when one of the electrode and the spacer is smaller than the other, the area of the bonding surface of the electrode and the spacer is consistent with the area of the bonding surface on the smaller side).
[0018] Here, in the method for producing a laminate for a secondary battery of the present invention, it is preferable that the adhesive material is formed of a polymer. When an adhesive material formed of a polymer is used, the electrode and the separator can be bonded well.
[0019] In the method for producing a secondary battery laminate of the present invention, the polymer preferably includes a low Tg polymer having a glass transition temperature of 25° C. or less. When a polymer including a low Tg polymer is used as an adhesive, the bonding strength between the electrode and the separator can be further improved.
[0020] In the present invention, the "glass transition temperature" can be measured in accordance with JIS K7121.
[0021] Furthermore, in the method for manufacturing a secondary battery laminate of the present invention, preferably in the above step (A), an adhesive composition comprising the above adhesive material and a solvent is supplied to the above bonding surface, and the amount of coarse particles having a diameter of 10 μm or more contained in the above adhesive composition is 100 ppm or less. If the amount of coarse particles is below the above upper limit, the energy density of the secondary battery made using the secondary battery laminate can be increased.
[0022] Here, in the present invention, the "amount of coarse particles" can be measured using the measurement method described in Examples of this specification.
[0023] In the method for producing a laminate for a secondary battery of the present invention, it is preferred that in the step (A), the adhesive material is formed at one or more locations on the bonding surface, and the area of the adhesive material formed at each location is 25 μm 2 Above and 250000μm 2 If the formation area per one location of the adhesive material is within the above range, the electrode and the separator can be bonded well, and the laminate for secondary batteries can be efficiently manufactured.
[0024] In the method for producing a secondary battery laminate of the present invention, it is preferred that the adhesive material is formed by an inkjet method in the step (A). If the adhesive material is formed by an inkjet method, the electrode and the separator can be more well bonded.
[0025] Effects of the Invention
[0026] According to the present invention, it is possible to efficiently manufacture a laminate for a secondary battery while ensuring the adhesive force between an electrode and a separator. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is an explanatory diagram showing a schematic structure of an example of a manufacturing apparatus for a laminated body for a secondary battery.
[0028] Figure 2 This is a plan view showing an example of a coating pattern of the adhesive composition. DETAILED DESCRIPTION
[0029] Hereinafter, embodiments of the present invention will be described in detail.
[0030] Here, the manufacturing method of the secondary battery laminate of the present invention can be used when manufacturing a secondary battery laminate formed by laminating an electrode (positive electrode and / or negative electrode) with a separator. Moreover, the secondary battery laminate manufactured using the manufacturing method of the secondary battery laminate of the present invention can be used when manufacturing secondary batteries such as non-aqueous secondary batteries (e.g., lithium ion secondary batteries).
[0031] Furthermore, the method for producing a laminate for a secondary battery of the present invention can be used particularly preferably when producing a laminate for a secondary battery continuously.
[0032] (Method for producing laminate for secondary battery)
[0033] The method for producing a secondary battery laminate of the present invention is a method for producing a secondary battery laminate by laminating an electrode and a separator. In the method for producing a secondary battery laminate of the present invention, the electrode and the separator are laminated to each other at a temperature of 0.1 g / m 2 Above and 100g / m 2After the following amount forms the process (A) of the bonding material on the bonding surface of at least one of the electrode and the spacer, the process (B) of transporting the electrode and the spacer to the bonding start position without contacting the bonding surface of the bonding material with other components is implemented, and then the process (C) of bonding the electrode and the spacer via the bonding surface is implemented, so as to manufacture the stack for secondary battery. Like this, if the bonding surface formed by the bonding material is not contacted with other components and the electrode and the spacer are transported to the bonding start position for bonding, the battery component (electrode and / or spacer) formed by the bonding material will not adhere. In addition, if the amount of the bonding material is formed within a specified range, even if the battery component (electrode and / or spacer) formed by the bonding material is directly used for bonding, the electrode and the spacer can be fully bonded. Therefore, the stack for secondary battery can be efficiently manufactured.
[0034] <Laminate for secondary battery>
[0035] The secondary battery laminate manufactured by the manufacturing method of the present invention laminates the electrode and the separator via the laminating surface. Here, the electrode that is laminated with the separator to form the secondary battery laminate may be only the positive electrode, only the negative electrode, or both the positive electrode and the negative electrode. In addition, when both the positive electrode and the negative electrode are laminated with the separator to form a secondary battery laminate, the number of positive electrodes, negative electrodes, and separators in the secondary battery laminate may be 1, or more than 2.
[0036] That is, the structure of the laminate for secondary batteries produced by the production method of the present invention may be any of the following (1) to (6).
[0037] (1) Positive electrode / separator
[0038] (2) Negative electrode / separator
[0039] (3) Positive electrode / separator / negative electrode
[0040] (4) Positive electrode / separator / negative electrode / separator
[0041] (5) Separator / positive electrode / separator / negative electrode
[0042] (6) A structure in which a plurality of positive electrodes and negative electrodes are alternately stacked with a separator (for example, "separator / negative electrode / separator / positive electrode / separator / negative electrode ... separator / positive electrode" etc.)
[0043] In addition, a laminate for a secondary battery having a plurality of electrodes and / or separators can be produced by repeatedly performing the above-mentioned steps (A) to (C).
[0044] <Electrode>
[0045] Here, the electrode is not particularly limited, and for example, an electrode formed of an electrode substrate having an electrode composite material layer formed on one or both sides of a current collector, or an electrode formed of an electrode substrate having an electrode composite material layer and further having a porous membrane layer formed on the electrode composite material layer can be used.
[0046] In addition, as current collector, electrode composite material layer and porous film layer, there is no particular limitation, and for example, any current collector, electrode composite material layer and porous film layer that can be used in the field of secondary batteries, such as those recorded in Japanese Patent Publication No. 2013-145763, can be used. Here, the porous film layer refers to a layer containing non-conductive particles such as recorded in Japanese Patent Publication No. 2013-145763.
[0047] Furthermore, the electrode used for manufacturing the laminate for secondary batteries may be wound into a roll or may be cut in advance.
[0048] <Spacer>
[0049] The separator is not particularly limited, and for example, a separator formed of a separator substrate or a separator having a porous membrane layer formed on one or both surfaces of a separator substrate can be used.
[0050] The separator substrate and the porous membrane layer are not particularly limited, and any separator substrate and porous membrane layer that can be used in the field of secondary batteries, such as those described in Japanese Patent Application Laid-Open Nos. 2012-204303 and 2013-145763, can be used.
[0051] The separator used in the production of the secondary battery stack may be rolled or cut in advance. However, from the viewpoint of efficiently and continuously producing the secondary battery stack, it is preferred to use a separator rolled as the separator.
[0052] <Adhesive Materials>
[0053] Furthermore, as a bonding material for bonding the electrode to the spacer, as long as the electrode and the spacer can be bonded and the battery reaction is not hindered, there is no particular limitation, and any bonding material used in the field of secondary batteries can be used. Among them, from the viewpoint of making the electrode and the spacer bond well, as a bonding material, a bonding material formed by a polymer is preferably used. In addition, the polymer constituting the bonding material can be only one kind, or it can be more than two kinds.
[0054] Here, the polymer that can be used as the adhesive material is not particularly limited, and examples thereof include: fluorine-based polymers such as polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP) copolymers; conjugated diene polymers such as styrene-butadiene copolymers (SBR) and acrylonitrile-butadiene copolymers (NBR); hydrogenated products of conjugated diene polymers; polymers containing (meth) alkyl acrylate monomer units (acrylic polymers); polyvinyl alcohol polymers such as polyvinyl alcohol (PVA), etc.
[0055] In addition, in the present invention, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.
[0056] Furthermore, the shape of the adhesive material formed of a polymer is not particularly limited, and may be granular, non-granular, or a combination of granular and non-granular forms.
[0057] In addition, when the adhesive material formed by the polymer is granular, the granular adhesive material can be a particle of a single-phase structure formed by a single polymer, or a particle of a heterogeneous structure formed by physically or chemically combining two or more different polymers. Here, as a specific example of a heterogeneous structure, there can be cited: a core-shell structure in which the central part (core part) and the outer shell part (shell part) of a spherical particle are formed by different polymers; a side-by-side structure as a structure in which two or more polymers are juxtaposed, etc. In addition, in the present invention, the "core-shell structure" includes a structure in which the outer surface of the core part is completely covered by the shell part, and a structure in which the outer surface of the core part is partially covered by the shell part. Moreover, in the present invention, even if the outer surface of the core part appears to be completely covered by the shell part in appearance, if a hole connecting the inside and outside of the shell part is formed, the shell part is a shell part that partially covers the outer surface of the core part.
[0058] In addition, when the adhesive material formed by the polymer is granular, the volume average particle size of the granular adhesive material is preferably 0.1 μm or more, more preferably 0.15 μm or more, more preferably 0.18 μm or more, preferably 5 μm or less, more preferably 3 μm or less, and more preferably 2 μm or less. If the volume average particle size of the granular adhesive material is above the above lower limit, the adhesion between the electrode and the separator can be improved. In addition, if the volume average particle size of the granular adhesive material is below the above upper limit, the energy density of the secondary battery made using the secondary battery laminate can be improved.
[0059] In the present invention, the “volume average particle size” refers to a particle size at which the cumulative volume calculated from the smaller diameter side accounts for 50% in a volume-based particle size distribution measured by a laser diffraction method.
[0060] Furthermore, in the case where the granular adhesive material includes a polymer having a core-shell structure, the volume average particle size of the polymer having a core-shell structure is preferably 0.1 μm or more, more preferably 0.15 μm or more, more preferably 0.2 μm or more, preferably 5 μm or less, more preferably 3 μm or less, and more preferably 2 μm or less. If the volume average particle size of the adhesive material formed by the polymer having a core-shell structure is above the above lower limit, the adhesion between the electrode and the separator can be improved. In addition, if the volume average particle size of the adhesive material formed by the polymer having a core-shell structure is below the above upper limit, the energy density of the secondary battery made using the secondary battery laminate can be improved.
[0061] In addition, in the case where the granular bonding material includes a polymer having a core-shell structure, in the bonding material formed by the polymer having a core-shell structure, the ratio (D10 / D50) of the particle size (D10) at which the cumulative volume calculated from the smaller diameter side becomes 10% relative to the volume average particle size (D50) in the volume-based particle size distribution is preferably 0.5 or more and 1.0 or less, more preferably 0.55 or more and 1.0 or less, and further preferably 0.6 or more and 1.0 or less. If D10 / D50 is above the lower limit, the bonding force between the electrode and the separator can be improved.
[0062] Furthermore, in the case where the granular bonding material includes a polymer having a core-shell structure, in the bonding material formed by the polymer having a core-shell structure, the ratio (D90 / D50) of the particle size (D90) at which the cumulative volume calculated from the smaller diameter side in the volume-based particle size distribution becomes 90% relative to the volume average particle size (D50) is preferably 1.5 or less, more preferably 1.45 or less, and further preferably 1.4 or less. If D90 / D50 is below the above upper limit, the bonding force between the electrode and the separator can be improved.
[0063] In addition, in the case where the granular bonding material includes a polymer with a core-shell structure, in the polymer with a core-shell structure, when the volume average particle diameter of the polymer with a core-shell structure is set to 100%, the diameter of the core portion is preferably 5% or more and less than 100%, more preferably 10% or more and less than 100%, and further preferably 20% or more and less than 100%. If the diameter of the core portion is above the above lower limit, the particle shape can be well maintained after being supplied to the bonding surface, and the electrode and the spacer are well bonded.
[0064] Furthermore, when the adhesive material is formed of a polymer, the polymer constituting the adhesive material preferably includes a low Tg polymer having a glass transition temperature of 25° C. or less. If the polymer constituting the adhesive material contains a low Tg polymer, the adhesion between the electrode and the separator can be improved. In addition, the glass transition temperature of the low Tg polymer is preferably above -120° C.
[0065] In addition, when the bonding material includes a polymer having a core-shell structure, the core portion of the polymer having a core-shell structure preferably has a glass transition temperature higher than that of the shell portion. If the glass transition temperature of the core portion is higher than that of the shell portion, the particle shape can be well maintained after being supplied to the bonding surface and the shell portion can exert a sufficiently high bonding force, so that the electrode and the spacer are well bonded.
[0066] Moreover, the glass transition temperature of the core of the polymer having a core-shell structure is preferably -40°C or more and 110°C or less, more preferably -40°C or more and 60°C or less, and further preferably -40°C or more and 25°C or less. If the glass transition temperature of the core is above the lower limit, the particle shape can be well maintained after being supplied to the bonding surface. In addition, if the glass transition temperature of the core is below the upper limit, the electrode and the separator can be well bonded.
[0067] In addition, the glass transition temperature of the shell portion of the polymer having a core-shell structure is preferably -40°C or more, more preferably -35°C or more, further preferably -30°C or more, preferably 50°C or less, more preferably 40°C or less, further preferably 30°C or less, and particularly preferably 25°C or less. If the glass transition temperature of the shell portion is above the above lower limit, the particle shape can be well maintained even after being supplied to the bonding surface. In addition, if the glass transition temperature of the shell portion is below the above upper limit, the electrode and the separator can be well bonded.
[0068] In this case, the polymer having a core-shell structure preferably has at least one glass transition temperature below 25°C.
[0069] <Step (A)>
[0070] In the step (A), the above-mentioned adhesive material is formed on the bonding surface of at least one of the electrode and the separator.
[0071] Here, the amount of adhesive material formed on the bonding surface needs to be 0.1 g / m 2 Above and 100g / m 2 Below, preferably 0.1g / m 2 Above and 50g / m 2 Below, more preferably 0.1g / m 2 Above and 10g / m2 Below, more preferably 0.1 g / m 2 Above 1g / m 2 If the amount of adhesive material formed is 0.1g / m 2 If the amount of adhesive material formed is 100 g / m 2 Next, the laminate for secondary batteries can be produced efficiently.
[0072] Furthermore, in step (A), when the adhesive material is formed on both the bonding surface on the electrode side and the bonding surface on the separator side, the amount of the adhesive material formed on each bonding surface is set to 0.1 g / m 2 Above and 100g / m 2 The following will do.
[0073] In addition, the adhesive material can be supplied to the bonding surface in any state such as solid state, molten state, dissolved in a solvent, or dispersed in a solvent. Among them, the adhesive material is preferably supplied in a state dissolved in a solvent or dispersed in a solvent, and more preferably supplied in a state dispersed in a solvent.
[0074] Furthermore, in the case where the adhesive material is supplied to the bonding surface in a state dissolved in a solvent or dispersed in a solvent in step (A), that is, when the adhesive composition containing the adhesive material and the solvent is supplied to the bonding surface, the solvent of the adhesive composition is not particularly limited, and for example, water, an organic solvent, and a mixture thereof can be used. In addition, the organic solvent is not particularly limited, and examples thereof include: cyclopentane, cyclohexane and other cyclic aliphatic hydrocarbons; toluene, xylene and other aromatic hydrocarbons; methyl ethyl ketone, cyclohexanone and other ketones; ethyl acetate, butyl acetate, γ-butyrolactone, ε-caprolactone and other esters; acetonitrile, propionitrile and other nitriles; tetrahydrofuran, ethylene glycol diethyl ether and other ethers; methanol, ethanol, isopropanol, ethylene glycol, ethylene glycol monomethyl ether and other alcohols; and the like.
[0075] Among the above, from the viewpoint of efficiently producing a laminate for a secondary battery, as the solvent, water and alcohol are preferred, and water is more preferred.
[0076] In addition, the concentration of the adhesive material in the adhesive composition is preferably 1% by mass or more and 40% by mass or less, more preferably 1% by mass or more and 30% by mass or less, and further preferably 1% by mass or more and 15% by mass or less. If the concentration of the adhesive material is within the above range, the secondary battery stack can be further efficiently manufactured.
[0077] Furthermore, the viscosity of the adhesive composition is preferably 1 mPa·s or more and 50 mPa·s or less, more preferably 1 mPa·s or more and 40 mPa·s or less, and further preferably 1 mPa·s or more and 30 mPa·s or less. If the viscosity of the adhesive composition is within the above range, the adhesive composition can be easily supplied to a desired position on the bonding surface to obtain a desired formation amount, so that the electrode and the spacer can be well bonded.
[0078] In the present invention, "viscosity" refers to a static viscosity value at a temperature of 20°C measured using a Brookfield viscometer (B-type viscometer).
[0079] In addition, the surface tension of the adhesive composition is preferably more than 10mN / m, more preferably more than 15mN / m, more preferably more than 20mN / m, preferably less than 72mN / m, more preferably less than 70mN / m, and more preferably less than 65mN / m. If the surface tension of the adhesive composition is more than the above lower limit, the adhesive composition can be supplied to the bonding surface in a desired shape to obtain a desired formation amount, and the secondary battery laminate can be manufactured more efficiently. In addition, if the surface tension of the adhesive composition is less than the above upper limit, the adhesive composition can be supplied to the desired position on the bonding surface so that the electrode and the spacer are well bonded.
[0080] In addition, in the present invention, "surface tension" refers to a value measured in accordance with JIS K2241.
[0081] Furthermore, the amount of coarse particles having a diameter of 10 μm or more contained in the adhesive composition is preferably 100 ppm or less, more preferably 50 ppm or less, and further preferably 10 ppm or less. If the amount of coarse particles is below the above upper limit, the energy density of the secondary battery made using the secondary battery laminate can be increased. In addition, the coarse particles contained in the adhesive composition are usually formed by a granular adhesive material formed by a polymer.
[0082] Furthermore, the formation of the adhesive material on the bonding surface is not particularly limited, and can be carried out using methods such as inkjet, spray coating, drop coating, gravure coating, screen printing, etc. Among them, the method for forming the adhesive material is preferably inkjet from the viewpoint of high productivity and high degree of freedom in forming the shape.
[0083] In addition, the adhesive material can be formed on the whole surface of the bonding surface, or it can be formed only on a part of the bonding surface. And, in the case of forming the adhesive material only on a part of the bonding surface, the adhesive material is not particularly limited, and can be formed into any planar shape such as stripe, dot, mesh, etc. Wherein, from the viewpoint of improving the injection of the electrolyte when using the secondary battery stack to manufacture the secondary battery, the adhesive material is preferably formed into a dot. And, the dot-shaped adhesive material can be evenly configured (formed) on the whole surface of the bonding surface, or it can be arranged into a stripe, dot, mesh, etc., and configured (formed). Wherein, from the viewpoint of improving the injection of the electrolyte when using the secondary battery stack to manufacture the secondary battery, it is preferred that the dot-shaped adhesive material is arranged in a stripe and configured (formed). In addition, in the case of arranging the tiny dot-shaped adhesive material into a prescribed pattern, from the viewpoint of easily carrying out the formation and arrangement of the adhesive material, it is preferred that the adhesive composition is applied to the desired pattern by an inkjet method to form the adhesive material.
[0084] In addition, the cross-sectional shape of the adhesive material is not particularly limited, and can be a convex shape, a concave shape, or a concave shape, wherein, from the viewpoint of making the electrode and the spacer further bonded well, it is preferably a concave-convex shape. In addition, the cross-sectional shape of the adhesive material can be changed by, for example, adjusting the drying conditions when the adhesive material is formed using the adhesive composition.
[0085] Here, when the adhesive material is formed at one or more places, preferably at two or more places on the bonding surface, the formation area of the adhesive material at each place formed on the bonding surface is preferably 25 μm 2 More preferably 50 μm 2 More preferably, 100 μm 2 Above, preferably 250000 μm 2 Below, more preferably 200000 μm 2 Below, more preferably 100000 μm 2 If the bonding material is formed in an area of 25 μm 2 If the area of adhesive material per location is 250000 μm 2 Next, the laminate for secondary batteries can be produced efficiently.
[0086] In addition, the above-mentioned formation area can be adjusted by changing the amount, shape and range of the adhesive material or adhesive composition applied on the bonding surface. Specifically, for example, when the adhesive material is formed by an inkjet method using the adhesive composition, the formation area can be adjusted by changing the frequency of ejecting the adhesive composition from the nozzle of the inkjet head (the number of ejections at the same point).
[0087] <Process (B)>
[0088] In step (B), the electrode and the spacer are transported to the lamination start position without contacting the lamination surface formed with the adhesive material with other components. In this way, if other components are not in contact with the lamination surface formed with the adhesive material, problems such as adhesion will not occur, so an adhesive material with excellent adhesion can be used, and a secondary battery stack can be efficiently manufactured.
[0089] The conveyance of the electrode and the separator is not particularly limited, and can be carried out using any conveying mechanism such as rollers, belt conveyors, robots, suction belts, etc. Among them, from the viewpoint of further improving the production efficiency of the secondary battery stack, it is preferred to convey at least one of the electrode and the separator using rollers.
[0090] In addition, in the case where an adhesive material as an adhesive composition is supplied in process (A), the adhesive composition on the bonding surface can also be dried during the transportation of process (B). Here, drying is not particularly limited, and can be carried out using a heating device such as a heater, a dryer, a heating roller, etc. In addition, the temperature during drying of the electrode and / or the separator to which the adhesive composition is supplied is not particularly limited, preferably above 0°C, more preferably above 10°C, more preferably above 15°C, preferably below 200°C, more preferably below 150°C, and more preferably below 100°C. If the temperature during drying is above the above lower limit, the drying speed can be fully increased and the stack for secondary batteries can be efficiently manufactured. In addition, if the temperature during drying is below the above upper limit, the shape of the adhesive material after drying can be made good, so that the electrode and the separator are well bonded.
[0091] <Process (C)>
[0092] In step (C), the electrode and the separator are bonded to each other via the bonding surface. Here, bonding is not particularly limited, and can be performed by, for example, pressing and / or heating the laminated body in which the electrode and the separator are stacked via the bonding surface.
[0093] In step (C), the pressure applied to the stack, the temperature when the electrode and the separator are bonded together, and the time for pressurizing and / or heating the stack can be appropriately adjusted according to the type and amount of the adhesive used.
[0094] <An example of a manufacturing apparatus for a secondary battery laminate>
[0095] The production of the secondary battery stack using the production method of the secondary battery stack of the present invention is not particularly limited, and can be carried out using, for example, Figure 1 The manufacturing device 100 shown is used.
[0096] Here, Figure 1 The manufacturing device 100 shown is a device for manufacturing the following secondary battery stack 200, which is formed by stacking electrodes (positive electrode and negative electrode) and separators in the order of "positive electrode / separator / negative electrode / separator" from the upper side to the lower side. In addition, in the manufacturing device 100, the obtained secondary battery stack 200 is cut into appropriate sizes and then further stacked for use in the manufacture of secondary batteries.
[0097] The manufacturing apparatus 100 includes a negative electrode roll 10 formed by rolling a negative electrode 11, a first separator roll 20 and a second separator roll 30 formed by rolling separators 21 and 31, and a positive electrode stocker 40 for storing a pre-cut positive electrode 41. The manufacturing apparatus 100 also includes a plurality of (9 in the example shown) conveying rollers 1, a plurality of (3 sets in the example shown) pressing rollers 2, a plurality of (4 in the example shown) adhesive material feeders 60A, 60B, 60C, 60D, and a cutter 50.
[0098] In the manufacturing apparatus 100, first, a coating pattern is formed such as Figure 2 In the manner of the oblique stripes shown in FIG. 1 , an adhesive composition 61 containing an adhesive material is supplied from an adhesive material supplying machine 60A to the surface (the upper surface in the example shown) of the negative electrode 11 delivered from the negative electrode roller 10 and conveyed by the conveying roller 1 (step (A)). Figure 2 In the coating pattern of the oblique stripe shape shown, the angle formed by the direction perpendicular to the conveying direction is measured from the narrow angle side in a plan view as θ, the arrangement pitch is P, and the width is W. Then, the negative electrode 11 supplied with the adhesive material and the separator 21 fed from the first separator roller 20 are conveyed to the lamination start position where the press roller 2 is located (step (B)), and the lamination is performed by the press roller 2 (step (C)).
[0099] When the adhesive composition is supplied from the adhesive material supply machine 60A, in the manufacturing apparatus 100 , the conveying roller 1 between the adhesive material supply machine 60A and the press roller 2 may be a heating roller to dry the adhesive composition.
[0100] In the manufacturing apparatus 100, the coating pattern is formed into, for example, Figure 2The adhesive composition 61 containing the adhesive material is supplied from the adhesive material supplying machine 60B to the surface of the negative electrode 11 side of the stack of the negative electrode 11 and the separator 21 bonded with the adhesive material in the manner of the oblique stripe shape shown (step (A)). Then, the stack of the negative electrode 11 and the separator 21 supplied with the adhesive material and the separator 31 fed from the second separator roller 30 are conveyed to the bonding start position where the pressing roller 2 is located (step (B)), and bonding is performed by the pressing roller 2 (step (C)).
[0101] When the adhesive composition is supplied from the adhesive material supply machine 60B, in the manufacturing apparatus 100 , the conveying roller 1 between the adhesive material supply machine 60B and the press roller 2 may be a heating roller to dry the adhesive composition.
[0102] Furthermore, in the manufacturing apparatus 100, the coating pattern is formed into, for example, Figure 2 The bonding composition 61 containing the bonding material is supplied from the bonding material supplying machine 60C to the surface of the separator 31 side of the stack of the negative electrode 11 and the separators 21 and 31 bonded with the bonding material in the same oblique stripe shape as shown in the pattern (step (A)). Then, at the bonding start position, the positive electrode 41 is arranged on the separator 31 of the stack of the negative electrode 11 and the separators 21 and 31 supplied with the bonding material (step (B)), and bonding is performed by the pressing roller 2 (step (C)).
[0103] When the adhesive composition is supplied from the adhesive material supply machine 60C, in the manufacturing apparatus 100 , the conveying roller 1 between the adhesive material supply machine 60C and the press roller 2 may be a heating roller to dry the adhesive composition.
[0104] In the manufacturing apparatus 100, the coating pattern is formed into, for example, Figure 2 An adhesive composition 61 containing an adhesive material is supplied from an adhesive material supply machine 60D to the surface of the positive electrode side of a secondary battery stack 200 formed by stacking "positive electrode / spacer / negative electrode / spacer" in sequence from the upper side to the lower side in the same manner as the diagonal stripes with the same pattern as shown, and then the secondary battery stack 200 is cut by a cutting machine 50.
[0105] In addition, the stacked bodies obtained by cutting the stacked body 200 for secondary batteries using the cutter 50 are further stacked and then used for the production of secondary batteries.
[0106] (Method for manufacturing secondary battery)
[0107] The method for producing a secondary battery using the secondary battery laminate comprises: a step of producing the secondary battery laminate using the method for producing the secondary battery laminate of the present invention; and a step of assembling a secondary battery using the secondary battery laminate and an electrolyte solution (assembling step).
[0108] <Assembly process>
[0109] Here, as an electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent can generally be used. For example, when the secondary battery is a lithium ion secondary battery, a lithium salt can be used as a supporting electrolyte. As a lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. can be cited. Among them, since it is easily soluble in a solvent and shows a high degree of dissociation, LiPF6, LiClO4, CF3SO3Li are preferably used, and LiPF6 is particularly preferably used. In addition, the electrolyte can be used alone or in combination with two or more in any ratio. Generally, since there is a tendency that the lithium ion conductivity is higher when a supporting electrolyte with a high degree of dissociation is used, the lithium ion conductivity can be adjusted according to the type of supporting electrolyte.
[0110] Furthermore, as an organic solvent for the electrolyte, there is no particular limitation as long as it can dissolve the supporting electrolyte, and preferably, for example, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (EMC), vinylene carbonate (VC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc. In addition, a mixed solution of these solvents can also be used. Among them, carbonates are preferably used because of their high dielectric constant and wide stable potential region. Generally, since there is a tendency that the lower the viscosity of the solvent used, the higher the lithium ion conductivity, the lithium ion conductivity can be adjusted according to the type of solvent.
[0111] The concentration of the electrolyte in the electrolytic solution can be adjusted appropriately. In addition, a known additive can be added to the electrolytic solution.
[0112] Moreover, the secondary battery can be assembled in the following manner: the secondary battery laminate manufactured according to the manufacturing method of the secondary battery laminate of the present invention is further laminated with additional battery components (electrodes and / or spacers, etc.) as needed, and then the obtained laminate is wound, bent, etc. corresponding to the battery shape as needed, placed in a battery container, and the electrolyte is injected into the battery container and sealed. In addition, in order to prevent the internal pressure of the secondary battery from rising, overcharging and discharging, etc., overcurrent prevention elements such as fuses, PTC elements, metal mesh, lead plates, etc. can be provided as needed. In addition, the shape of the secondary battery can be, for example, any of coin-type, button-type, sheet-type, cylindrical, square, flat, etc.
[0113] Example
[0114] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In addition, in the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.
[0115] In the embodiments and comparative examples, the glass transition temperature, volume average particle size D50 and particle size distribution of the polymer constituting the adhesive material, the viscosity, surface tension and content of coarse particles with a diameter of 10 μm or more of the adhesive composition, the dry bonding strength between the electrode and the separator, and the electrolyte injection properties, output characteristics and cycle characteristics of the secondary battery were measured and evaluated by the following methods.
[0116] <Glass transition temperature>
[0117] The measurement was performed in accordance with JIS K7121 at a measurement temperature of -100°C to 180°C and a temperature increase rate of 5°C / min using a differential scanning calorimeter (DSC6220SII manufactured by Nano Technology).
[0118] <Volume average particle size D50 and particle size distribution>
[0119] The particle size distribution (volume basis) of the aqueous dispersion of the granular polymer was measured by a laser diffraction particle size distribution measuring device (manufactured by Shimadzu Corporation, product name "SALD-3100"). Then, in the measured particle size distribution, the particle size at which the cumulative volume calculated from the small diameter side is 50% is taken as the volume average particle size (D50) of each particle. In addition, using the measured particle size distribution, the particle size (D10) at which the cumulative volume calculated from the small diameter side is 10% and the particle size (D90) at which the cumulative volume calculated from the small diameter side is 90% are obtained, and D10 / D50 and D90 / D50 are calculated.
[0120] <Viscosity>
[0121] The static viscosity of the prepared adhesive composition was measured at a temperature of 20°C using a Brookfield viscometer (manufactured by Eiko Seiki Co., Ltd., DV1M).
[0122] <Surface tension>
[0123] The surface tension of the prepared adhesive composition at a temperature of 25° C. was measured using a surface tension measuring apparatus (DY-700, manufactured by Kyowa Interface Chemical Co., Ltd.) in accordance with JIS K2241.
[0124] <Content of coarse particles>
[0125] Measure the mass (B) of a nylon mesh with an average pore size of 10 μm and place it in a funnel. Then, inject 100 g of the adhesive composition and filter. Pour ion exchange water into it, wash until it is no longer turbid, and dry it in an oven at 90°C for more than 60 minutes. After cooling, measure the mass (A) of the nylon mesh and determine the amount of mesh residue. The amount of mesh residue, that is, the amount of coarse particles with a particle size of 10 μm or more in the adhesive composition, is calculated by the following formula.
[0126] Content of coarse particles (ppm) = (AB) / (C×D / 100)×1000000
[0127] A: Mass of net + dried material (g)
[0128] B: Mass of the net (g)
[0129] C: Mass of the filtered adhesive composition (g)
[0130] D: Total solid content concentration of adhesive composition (%)
[0131] <Formation area of adhesive material per location>
[0132] The adhesive material forming area S per location 50 The calculation was performed as follows: a laser microscope (manufactured by KEYENCE CORPORATION, VR-3100) was used to measure the 2 The major diameter x and minor diameter y of the adhesive material in the form of dots formed in the area, z = (x + y) / 2 is set as the average diameter, and S = 1 / 4πz is calculated 2 The area of each point was calculated as the average of the areas S of 50 points and was taken as the area S of the adhesive material formed per one point. 50 .
[0133] <Dry bonding>
[0134] The positive electrode, negative electrode and separator prepared in the embodiments and comparative examples were cut into pieces with a width of 10 mm and a length of 50 mm, respectively, and the positive electrode and separator, as well as the negative electrode and separator, were stacked. The stack was pressed at a speed of 10 m / min by roller pressing at a temperature of 70°C and a load equivalent to a pressure of 1 MPa to prepare test pieces.
[0135] The current collector side of the electrode (positive or negative electrode) of the test piece is facing down, and a transparent tape is pasted on the surface of the electrode. At this time, the transparent tape specified in JIS Z1522 is used as the transparent tape. In addition, the transparent tape is fixed to a horizontal test bench. Then, one end of the spacer is stretched vertically upward at a stretching speed of 50 mm / min to measure the stress during peeling.
[0136] The measurement was performed 3 times for each of the laminated body having the positive electrode and the separator and the laminated body having the negative electrode and the separator, for a total of 6 times, and the average value of the stress was calculated and used as the peel strength. The adhesion between the electrode and the separator was evaluated according to the following criteria. The greater the peel strength, the higher the adhesion.
[0137] A: Peel strength is 3N / m or more
[0138] B: Peel strength is 1 N / m or more and less than 3 N / m
[0139] C: Peel strength less than 1N / m
[0140] <Electrolyte injection properties>
[0141] The manufactured secondary battery stack was packaged with an aluminum packaging material outer packaging as the battery outer packaging, and the electrolyte (solvent: ethylene carbonate / diethyl carbonate / vinyl carbonate = 68.5 / 30 / 1.5 (volume ratio), electrolyte: LiPF6 with a concentration of 1 M) was injected at different injection times without residual air.
[0142] Then, the shortest injection time at which the electrolyte does not overflow during injection was determined and evaluated according to the following criteria: The shorter the shortest injection time, the better the electrolyte injection property.
[0143] A: The shortest injection time is less than 100 seconds
[0144] B: The shortest injection time is more than 100 seconds and less than 300 seconds
[0145] C: The shortest injection time is more than 300 seconds and less than 500 seconds
[0146] D: The shortest injection time is more than 500 seconds
[0147] <Output Characteristics>
[0148] The secondary battery was charged to 4.3 V by constant current constant voltage (CCCV) at 25°C. Then, the capacity was determined when the battery was discharged to 3.0 V by 0.2 C constant current method and when the battery was discharged to 3.0 V by 1 C constant current method at -10°C.
[0149] Then, the discharge capacity retention rate represented by the capacitance ratio (=(1C capacitance / 0.2C capacitance)×100(%)) was calculated. These measurements were performed on the secondary battery of 5 battery cells, and the average value of the discharge capacity retention rate of each battery cell was used as the low-temperature output characteristic, which was evaluated according to the following criteria. The larger the value, the better the output characteristic.
[0150] A: Low temperature output characteristics are more than 80%
[0151] B: Low temperature output characteristic is more than 70% and less than 80%
[0152] C: Low temperature output characteristics are 60% or more and less than 70%
[0153] D: Low temperature output characteristics less than 60%
[0154] <Cyclic Characteristics>
[0155] Under a temperature of 45°C, the secondary battery was charged to 4.4V and discharged to 3.0V by a constant current method of 0.5C, and the above charge and discharge were repeated for 200 cycles. Then, the charge and discharge capacity retention rate represented by the ratio of the capacitance at the end of 200 cycles to the capacitance at the end of 5 cycles (= (capacity at the end of 200 cycles / capacity at the end of 5 cycles) × 100 (%)) was calculated. These measurements were performed on the secondary batteries of 5 battery cells, and the average value of the charge and discharge capacity retention rate of each battery cell was used as the high-voltage cycle characteristics, which were evaluated by the following benchmarks. The larger the value, the better the cycle characteristics.
[0156] A: High-pressure cycle characteristics are more than 95%
[0157] B: High-pressure cycle characteristics are 90% or more and less than 95%
[0158] C: High-pressure cycle characteristics less than 90%
[0159] (Example 1)
[0160] <Preparation of adhesive materials>
[0161] As a granular first adhesive material formed by a polymer having a core-shell structure, an aqueous dispersion of core-shell particles is prepared, wherein the core-shell particles have a core portion formed by a polymer having a glass transition temperature of 108°C and a shell portion formed by a polymer having a glass transition temperature of -17°C that partially covers the outer surface of the core portion.
[0162] Furthermore, as a second adhesive material in the form of particles composed of a polymer having a single-phase structure, an aqueous dispersion of a styrene-butadiene copolymer (SBR) was prepared.
[0163] Then, the glass transition temperature, volume average particle size D50 and particle size distribution of the polymer constituting the adhesive material were measured.
[0164] <Preparation of Adhesive Composition>
[0165] 10 parts of the second adhesive material aqueous dispersion in terms of solid content and 100 parts of the first adhesive material aqueous dispersion in terms of solid content were mixed in a stirring container and diluted with ion exchange water to obtain an adhesive composition having a solid content concentration of 10%.
[0166] Then, the viscosity, surface tension, and content of coarse particles having a diameter of 10 μm or more of the adhesive composition were measured.
[0167] <Formation of Negative Electrode>
[0168] In a 5Mpa pressure-resistant container with a stirrer, 33 parts of 1,3-butadiene, 3.5 parts of itaconic acid, 63.5 parts of styrene, 0.4 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion exchange water and 0.5 parts of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the polymerization was initiated by heating to 50°C. When the polymerization conversion rate reached 96%, the reaction was terminated to obtain a mixture containing a binder (SBR) for a negative electrode composite material layer. In the above mixture containing a binder for a negative electrode composite material layer, a 5% aqueous solution of sodium hydroxide was added, and after adjusting the pH to 8, unreacted monomers were removed by heating and reduced pressure distillation. Thereafter, it was cooled to below 30°C to obtain an aqueous dispersion containing the desired binder for a negative electrode composite material layer.
[0169] Next, 100 parts of artificial graphite (volume average particle size: 15.6 μm) as a negative electrode active material, 1 part of carboxymethyl cellulose sodium salt (Nippon Paper Industries Co., Ltd., product name "MAC350HC") as a viscosity modifier were mixed with ion exchange water, and the solid content concentration was adjusted to 68%, and then further mixed at 25°C for 60 minutes. Furthermore, after the solid content concentration was adjusted to 62% by ion exchange water, it was further mixed at 25°C for 15 minutes. To the obtained mixed solution, 1.5 parts of the above-mentioned aqueous dispersion containing a binder for a negative electrode composite material layer and ion exchange water were added in an equivalent amount of solid content, and the final solid content concentration was adjusted to 52%, and further mixed for 10 minutes. It was degassed under reduced pressure to obtain a slurry composition for a secondary battery negative electrode with good fluidity.
[0170] The obtained secondary battery negative electrode slurry composition is applied to a copper foil with a thickness of 20 μm as a current collector by a notch wheel coater in a manner that the film thickness after drying is about 150 μm, and dried. The drying is carried out by conveying the copper foil in an oven at 60°C for 2 minutes at a speed of 0.5 m / min. Thereafter, a heat treatment is performed at 120°C for 2 minutes to obtain a negative electrode raw material before pressing. The negative electrode raw material before pressing is rolled by a roller press to obtain a negative electrode after pressing with a thickness of 80 μm of the negative electrode composite material layer.
[0171] <Formation of positive electrode>
[0172] 100 parts of LiCoO2 with a volume average particle size of 12 μm as a positive electrode active material, 2 parts of acetylene black (Denki Kagaku Kogyo Co., Ltd., trade name "HS-100") as a conductive material, 2 parts of polyvinylidene fluoride (KUREHA CORPORATION, product name "#7208") as a binding material in terms of solid content, and N-methylpyrrolidone as a solvent were mixed to make a total solid content concentration of 70%. They were mixed by a planetary mixer to obtain a slurry composition for a secondary battery positive electrode.
[0173] The obtained secondary battery positive electrode slurry composition was applied to an aluminum foil with a thickness of 20 μm as a current collector by a notch wheel coater in a manner that the film thickness after drying was about 150 μm, and dried. The drying was performed by conveying the aluminum foil in a 60° C. oven at a speed of 0.5 m / min for 2 minutes. Thereafter, a heat treatment was performed at 120° C. for 2 minutes to obtain a positive electrode raw material.
[0174] Then, the obtained positive electrode raw material was rolled using a roll press to obtain a positive electrode having a positive electrode composite material layer.
[0175] <Preparation of spacers>
[0176] A spacer made of polypropylene (PP) (product name: "CELLGARD 2500") was prepared.
[0177] <Manufacturing of laminate for secondary battery>
[0178] Using the prepared adhesive composition, negative electrode, positive electrode and separator, Figure 1 The manufacturing apparatus shown manufactures a laminate for a lithium ion secondary battery and cuts it.
[0179] As the adhesive material supplier, an ink jet type adhesive material supplier having an ink jet head (manufactured by Konica Corporation, KM1024 (shear mode type)) was used.
[0180] In addition, the conveying speed is 10m / min, and the adhesive composition is as follows Figure 2 The coating pattern having the stripe shape shown (θ: 45°, P: 200 μm, W: 30 μm) was supplied, and the other manufacturing conditions were the conditions shown in Table 1.
[0181] In addition, the supplied adhesive composition is dried by using a heating roller as a part of the conveying roller. Then, the dried adhesive material is observed by a laser microscope, and the adhesive material is a tiny dot. That is, there are a plurality of tiny dot adhesive materials arranged in a pattern of oblique stripes in the bonding surface. In addition, the average height (thickness) and the maximum height (thickness) of the adhesive material are confirmed by observing the cross section with a laser microscope, and the cross section is a concave-convex shape, with an average height of 1 μm and a maximum height of 3 μm.
[0182] Then, the dry adhesive strength of the laminate for secondary batteries was evaluated.
[0183] <Manufacturing of Secondary Battery>
[0184] Five cut secondary battery stacks were stacked and pressed at a temperature of 70° C. and a pressure of 1 MPa for 10 seconds to prepare a stack.
[0185] The stacked body was packaged with an aluminum packaging material as the outer packaging of the battery, and an electrolyte was injected (solvent: ethylene carbonate / diethyl carbonate / vinyl carbonate = 68.5 / 30 / 1.5 (volume ratio), electrolyte: LiPF6 with a concentration of 1M). Afterwards, the opening of the aluminum packaging material shell was sealed by heat sealing at 150°C to manufacture a stacked lithium-ion secondary battery with a capacity of 800mAh.
[0186] Then, the electrolyte injection property, output characteristics, and cycle characteristics of the secondary battery were evaluated. The results are shown in Table 1.
[0187] (Example 2)
[0188] In the manufacture of the secondary battery stack, the adhesive composition is supplied in a dot-shaped coating pattern (diameter: 50 μm, distance between dots: 200 μm), and otherwise, the same method as in Example 1 is used to prepare or manufacture adhesive materials, adhesive compositions, negative electrodes, positive electrodes, separators, secondary battery stacks, and secondary batteries. In addition, the adhesive material is in a tiny dot shape. That is, there are a plurality of tiny dot-shaped adhesive materials in the bonding surface to form a plurality of large dots. In addition, the cross section of the adhesive material is observed by a laser microscope, and the cross section is a concave-convex shape. Then, the evaluation is performed in the same manner as in Example 1. The results are shown in Table 1.
[0189] (Example 3)
[0190] When manufacturing the stacked body for secondary batteries, the manufacturing conditions are changed as shown in Table 1. In addition, the same method as in Example 1 is used to prepare or manufacture adhesive materials, adhesive compositions, negative electrodes, positive electrodes, spacers, stacked bodies for secondary batteries, and secondary batteries. In addition, the adhesive material is in a tiny dot shape. That is, there are a plurality of tiny dot-shaped adhesive materials arranged in a pattern of oblique stripes in the bonding surface. In addition, the cross section of the adhesive material is observed by a laser microscope, and the cross section is a convex shape. Then, the evaluation is carried out in the same manner as in Example 1. The results are shown in Table 1.
[0191] (Example 4)
[0192] As the first adhesive material, a granular polymer of a single-phase structure with a glass transition temperature of 15°C is used. When manufacturing a stack for a secondary battery, the stripe shape (θ: 45°, P: 400μm, W: 30μm) and the manufacturing conditions are changed as shown in Table 1. When manufacturing a secondary battery, 5 cut stacks for a secondary battery are overlapped and pressed at a temperature of 40°C and a pressure of 1MPa for 5 seconds to form a stack. Otherwise, the same method as in Example 1 is used to prepare or manufacture an adhesive material, an adhesive composition, a negative electrode, a positive electrode, a separator, a stack for a secondary battery, and a secondary battery. In addition, the adhesive material is in the form of tiny dots. That is, there are a plurality of tiny dots of adhesive materials arranged in a pattern of oblique stripes on the bonding surface. In addition, the cross-section of the adhesive material is observed by a laser microscope, and the cross-section is concave-convex. Then, the evaluation is performed in the same manner as in Example 1. The results are shown in Table 1.
[0193] (Comparative Example 1)
[0194] As a spacer, the adhesive composition was applied in a dot-shaped coating pattern on one side (for spacer 21) or both sides (for spacer 31) of a spacer made of polypropylene (PP) (trade name "CELLGARD 2500") by a gravure roller, and hot air drying was performed at a temperature of 70°C (drying time: 6 seconds). The adhesive material feeders 60A to 60D and the heating roller were not provided, and the adhesive composition feeders 60A to 60D and the heating roller were not provided. Figure 1 A manufacturing device with the same structure as the manufacturing device shown in the figure manufactures a stack for secondary batteries, and in addition, the same method as in Example 1 is used to prepare or manufacture adhesive materials, adhesive compositions, negative electrodes, positive electrodes, spacers, stacks for secondary batteries, and secondary batteries. In addition, the adhesive material is in a tiny dot shape. That is, there are a plurality of large points formed by a plurality of tiny dot-shaped adhesive materials in the bonding surface. In addition, the cross section of the adhesive material is observed by a laser microscope, and the cross section is a convex shape. Then, the evaluation is carried out in the same manner as in Example 1. The results are shown in Table 1.
[0195] Furthermore, when manufacturing the laminate for secondary batteries, the separator wound in a roll shape causes blocking, so the laminate is manufactured while being peeled off.
[0196] [Table 1]
[0197]
[0198] As can be seen from Table 1, in Examples 1 to 4, the adhesion between the electrode and the separator can be ensured and the secondary battery stack can be efficiently manufactured. On the other hand, as can be seen from Table 1, in Comparative Example 1, the adhesion between the electrode and the separator cannot be sufficiently ensured due to the peeling of the adhesive material of the adhesion of the separator, and the secondary battery stack cannot be efficiently manufactured.
[0199] Industrial Applicability
[0200] According to the present invention, it is possible to efficiently manufacture a laminate for a secondary battery while ensuring the adhesive force between an electrode and a separator.
[0201] Description of Reference Numerals
[0202] 1: Transport roller
[0203] 2: Pressing roller
[0204] 10: Negative roller
[0205] 11: Negative electrode
[0206] 20: First spacer roller
[0207] 30: Second spacer roller
[0208] 21, 31: Spacers
[0209] 40: Positive electrode storage tank
[0210] 41: Positive electrode
[0211] 50: Cutting machine
[0212] 60A, 60B, 60C, 60D: Adhesive material supply machine
[0213] 61: Adhesive materials
[0214] 100: Manufacturing Device
[0215] 200: Laminated body for secondary battery
Claims
1. A method for manufacturing a secondary battery laminate, which is a method for manufacturing a secondary battery laminate formed by laminating an electrode and a separator, comprising the following steps: Step (A), forming an adhesive material on a bonding surface of at least one of the electrode and the separator; Step (B), after step (A), conveying the electrode and the spacer to a lamination start position without allowing the lamination surface formed with the adhesive material to contact other members; Step (C), after step (B), laminating the electrode and the separator via the laminating surface, The amount of the adhesive material formed in the step (A) is 0.1 g / m 2 Above and 100g / m 2 the following, The adhesive material is patterned on the bonding surface so as to have a stripe-like planar shape.
2. The method for producing a laminate for a secondary battery according to claim 1, wherein: The cross-sectional shape of the formed adhesive material is a concavo-convex shape or a concave shape.
3. The method for producing a laminate for a secondary battery according to claim 1, wherein: The adhesive material in the form of dots is arranged in a stripe shape and is formed on the bonding surface.
4. The method for producing a laminate for a secondary battery according to claim 1, wherein: In the step (A), the adhesive material is formed by supplying an adhesive composition containing the adhesive material and a solvent to the bonding surface. The surface tension of the adhesive composition is 20 mN / m or more and 65 mN / m or less.
5. The method for producing a laminate for a secondary battery according to claim 1, wherein: The bonding material is formed of a polymer.
6. The method for producing a laminate for a secondary battery according to claim 5, wherein: The polymer includes a low Tg polymer having a glass transition temperature of 25° C. or less.
7. The method for producing a laminate for a secondary battery according to any one of claims 1 to 6, wherein: In the step (A), the adhesive material is formed by an inkjet method.
Citation Information
Patent Citations
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A
Slurry composition for secondary battery porous film, secondary battery electrode, secondary battery separator, and secondary battery
JP2013145763A
A method for manufacturing a separator, a separator manufactured by the method, and an electrochemical element equipped therewith.
JP2014534570A
Adhesive agent for lithium ion secondary batteries, separator with adhesion layer, electrode with adhesion layer, and lithium ion secondary battery
JP2015041603A